Separation of enantiomers by chromatography as a vehicle for chiral catalysis : abridged review - Šunjić, Vitomir (Array, 2009)
Summary: Chiral, or asymmetric catalysis is the most efficient approach to chiral molecules in the enantio-merically enriched form. Organocatalysis and organometallic catalysis are nowadays the methods of choice in this field. In the first case enantiomerically pure chiral organic molecules of different symmetry classes exhibit catalytic effect, in the second one chiral organic molecule acts as the ligand in the organometallic complex that exerts catalytic activity. In both cases small amount, milligrams or grams, of enantiopure organic or organometallic catalyst suffice to produce substantial amounts, grams or tons, of chiral products of academic or commercial interest. Due to the need for limited quantities of chiral organic molecules in the optically pure form to act as the catalysts or be the part of the catalytic systems, preparative chromatographic separation, and in particular simulated moving bed (SMB) chromatographic resolution of racemic material, represent valuable approach. Examples of separation of racemates by chiral chromatography and SMB technology to catalytically useful enantiomers are presented, and application of enantiomers from different symmetry classes in efficient catalytic processes is highlighted